ANALISIS PEMASANGAN FILTER PASIF DAN AKTIF TERHADAP KANDUNGAN HARMONISA DAN RUGI-RUGI DAYA GARDU DISTRIBUSI KA 2085 DI PT. PLN (Persero) DISTRIBUSI BALI RAYON MENGWI - Budi Aryawan, I Putu; Ibi Weking, Antonius; Rinas, I Wayan (Jurnal SPEKTRUM; Vol 5 No 1 (2018): Jurnal SPEKTRUM, 2018)
Operation of nonlinear loads can cause harmonic distortion in the voltage and current waveforms that result in abnormal electrical system condition. Content THD (Total Harmonics Distortion) an excess flow can cause power quality systems become worse, thus causing the system power factor is lower. Active filter and Passive filter which aims to reduce harmonics that arise. Analysis THD simulation and measurement results in accordance with IEEE 519-2014 and analysis designing of a passive filter and active filter is right to suppress harmonic distortion. The analysis shows that the installation of active filters causes the current and voltage THD contents to comply with the standard IEEE 519-2014 standards is ?12% and 5%. The use of passive and active filters can reduce THDi content to 8.45% and 3.07%, respectively. While for THDv decreased respectively to 3.68% and 3.45% which already meet the IEEE 519-2014 standards. Power losses decreased respectively to 4.36 kW and 3.86 kW. Installation of active filters is better for reducing THD (Total Harmonics Distortion) and power losses in KA 2085 transformers.